Curriculum evaluation in higher education : a case study of a Physics pre-service teachers curriculum in Indonesia - Maison (Curtin University, 2013)
Recent government policies about the curriculum and the needs of stakeholders for qualified graduates have provided arguments for physics pre-service teacher education programmes in Indonesia to be evaluated. These arguments have increased due to the rapid changes in local, national, and international dynamics.The purpose of this research was to evaluate by means of a case study the physics education curriculum for pre-service teachers by examining five levels of curriculum representation (the ideal, the formal/written, the perceived, the operational, and the experiential curriculum) in one Indonesian higher education institution. This case study involved (1) collecting and analysing information from government and institution documents, (2) developing and administrating surveys to assess the pre-service teachers’ and graduates’ as well as their lecturers’ perceptions of the physics education curriculum, (3) observations of teaching and learning in three different subjects, (4) oneon- one interviews with three physics lecturers, and (5) five focus group interviews with the pre-service teachers and graduates.Within this case study, the research design that was developed to answer the four research questions was a mixed method convergent parallel design for collecting and analysing quantitative and qualitative data. In this design, the researcher implemented the quantitative and qualitative methods during the same timeframe and with equal weight. While the quantitative and qualitative data were collected and analysed separately, the two sets of results were merged using strategies so that those could be interpreted together.The Indonesian government has provided generic guidelines for the ideal curriculum that is appropriate for physics pre-service teacher programmes as well as other programmes in all higher education institutions throughout Indonesia. In other words, the guidelines are expressed in very general and flexible terminologies. Therefore, by rewording them, every higher education institution can use the guidelines. However, the analyses associated with the formal/written curriculum suggest that the number of subjects and credits in the curriculum should be reduced because the curriculum was overloaded and the syllabi were overcrowded. Focus group interviews showed that several students had difficulties learning physics because some subjects in physics consisted of many theories and complex concepts. Additionally, they would like more physics content that is related to their future work as secondary school physics teachers rather than be required to study difficult physics theories.The actual process of teaching and learning in three subjects (General Physics I, Mechanics, and Laboratory Management) was observed with the focus on the content, the learning activities and lecturer’s role, the teaching resources and facilities, and the assessment. The observations, questionnaire, and interview results indicated that the lecturers provided assistance to students to learn, for example, by providing notes, examples, handouts, and library references. However, not many lecturers demonstrated enough interaction and recognition of their students' level of understanding. The lecturers’ approaches to teaching seemed to be content-centred rather than learnercentred. On the other hand, only a few pre-service teachers showed enthusiasm or were engaged in the teaching and learning process. In general, the pre-service teachers had surface approaches to learning physics. Nevertheless, lecturers, pre-service teachers as well as graduates were in agreement with the aims and objectives of the physics education curriculum.The results of this research make a distinct contribution to improve the curriculum within the field of secondary physics teacher education, which are summarised as basic assertions. In brief, the number of subjects and credits in the curriculum should be reduced; the curriculum should be more related to the pre-service teachers’ future jobs and the needs of stakeholders; the lecturers should use the physics methods that address the individuality of the pre-service teachers; and the resources, facilities and number of lecturers should be increased. These assertions have implications for the lecturers or physics teacher educators, curriculum developers, decision makers of higher education institution and future physics pre-service teachers.